Potensi Plant Growth Promoting Rhizobacteria (PGPR) Untuk Mengendalikan Tobacco Mosaic virus (TMV) Pada Tanaman Cabai - Yuneary Yunearty; Noor Aidawati; Mariana Mariana (www.ulm.ac.id, 2023)
The mosaic disease that causes TMV is a major pest of chili cultivation. Mosaic disease is significant because the losses it causes are quite significant. Environmentally friendly control of TMV can use PGPR. This study aims to study the potential of PGPR derived from reed roots, bamboo roots, kalakai roots and elephant grass roots in controlling TMV in chili plants. This study used a 1-factor Completely Randomized Design (CRD) with 6 treatments, K1(–), K2(+), A + TMV, B + TMV, C + TMV and D + TMV. PGPR is made using reed roots, bamboo roots, kalakai roots and elephant grass roots. The results of the study confirmed that PGPR derived from reed roots, bamboo roots, melakai roots and elephant grass roots had the potential to control TMV in large chili plants and stimulate the growth of chili plants, namely increasing the height of chili plants infected with TMV, increasing fruit and production. PGPR derived from bamboo roots has better performance than reed roots, elephant grass roots, and kalakai roots.